Extraction and utilization forecasts for the construction non-metallic minerals in post-war recovery period of Ukraine - Horoshkova, L.; Menshov, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The article provides modelling aimed at the management system design for the rational extraction and use of mineral resources of Ukraine applying the case of construction non-metallic minerals to ensure the country’s post-war recovery. The projection volumes for production and rational use formed taking into account the needs of technologically related industries have been suggested. The official statistical data analysis on the production volumes of construction stone, construction sand and expanded clay raw materials during the studied period (15 years) have been carried out. It has been found out that indicators’ fluctuations both in production volumes and their growth rates have a periodic, cyclical nature. They are correlated and related to the general economic condition of the construction industry and the country. It has been proven that solving the problem of minerals rational use is possible through their balanced extraction, namely putting correlation between extraction and utilization volumes. The authors’ economic-mathematical model of forecasting the development of complex systems has been used to forecast industry’s development. It has been proven that the model will allow managing the production of technologically related minerals depending on their utilization volumes. It has been proven that amid war conditions due to the destruction of the country’s infrastructure, there is a need to make model adjustments for balanced extraction and use of construction non-metallic minerals, taking into account generated construction waste and the needs of the post-war country’s and its infrastructure’s recovery. Modelling was carried out taking into account the new conditions of the industry’s and the country’s development. A five-year forecast has been made for the production and utilization of construction sand, construction stone and expanded clay.